Metals in Biology Applications of High-Resolution EPR to Metalloenzymes - Hanson, Graeme; Berliner, Lawrence (Biological Magnetic Resonance,, 2010)
Metals in Biology Applications of High Resolution EPR to Metalloenzymes Prof. Graeme R. Hanson, University of Queensland and Prof. Lawrence J. Berliner, University of Denver Metal ions in biology is an ever expanding area in science and medicine involving metal ions in proteins and enzymes, their biosynthesis, catalysis, electron transfer, metal ion trafficking, gene regulation and disease. While X-ray crystallography has provided snapshots of the geometric structures of the active site redox cofactors in these proteins, the application of high resolution EPR spectroscopy in conjunction with quantum chemistry calculations has enabled, in many cases, a detailed understanding of a metalloenzymes mechanism through investigations of the geometric and electronic structure of the resting, enzyme-substrate intermediates and product complexes. This volume, Part II of a two-volume set demonstrates the application of high resolution EPR spectroscopy in determining the geometric and electronic structure of active site metal ion centers in iron sulfur cluster containing metalloproteins, mononuclear molybdenum metalloenzymes, manganese-containing enzymes and novel metalloproteins. The following chapters, written by experts in their fields, include: An Introduction: John Pilbrow Electron Magnetic Resonance of Iron-sulfur Proteins in Electron Transfer Chains - Resolving Complexity: Richard Cammack, Fraser MacMillan Catalysis and Gene Regulation: Helmut Beinert Iron Sulfur Clusters in Radical SAM Enzymes: Spectroscopy and Coordination: Serge Gambarelli, Etienne Mulliez, Marc Fontecave EPR Studies of Xanthine Oxidoreductase and Other Molybdenum-containing Hydroxylases: Russ Hille High Resolution EPR Spectroscopy of Mo-enzymes. Sulfite Oxidases: Structural and Functional Implications: John Enemark, Andrei Astashkin, Arnold Raitsimring Dimethylsulfoxide (DMSO) Reductase, a Member of the DMSO Reductase Family of Molybdenum Enzymes: Graeme Hanson, Ian Lane The Manganese-Calcium Cluster of the Oxygen Evolving System: Synthetic Models, EPR Studies, and Electronic Structure Calculations: Marcin Brynda, David Britt Binuclear Manganese-dependent enzymes: Sarah Smith, Kieran Hadler, Gerhard Schenk, Graeme Hanson, Nataša Mitic EPR of Cobalt-Substituted Zinc Enzymes: Brian Bennett Hyperfine and Quadrupolar Interactions in Vanadyl Protein and Model Complexes. Theory and Experiment: Sarah Larsen, Dennis Chasteen.